GENDER EQUALITY IN RELIGIOUS COURT DECISIONS: A STUDY OF ALIMONY AND THE STATUS OF MAFQUD HUSBANDS FROM AN ISLAMIC FAMILY LAW PERSPECTIVE - Jamil, Nur Cahya; Alam, Syariful (JCH (Jurnal Cendekia Hukum), 2025)
The rising rate of female-initiated divorce in Indonesia highlights women's vulnerability due to neglected fundamental rights, specifically alimony, and the prevalence of mafqud (missing) husbands. This situation forces wives into a dilemma of legal uncertainty and structural economic burdens. This study aims to analyse the implementation of gender equality principles in Religious Court decisions concerning the protection of wives' economic rights in cases involving mafqud (missing) husbands, while also examining the consistency of legal application in judicial practice. The research employs a normative-juridical method, using statutory, conceptual, and case-study approaches, analysing three specific Religious Court decisions: PA Kendal (2023), PA Kaimana (2021), and PA Merauke (2011). The results indicate significant legal disparities in the adjudication of similar cases. Some courts maintain a formalistic approach that merely provides legal certainty regarding divorce status without restoring the wife's economic rights. Conversely, other courts have begun adopting a substantive justice approach by granting iddah maintenance (nafkah iddah) and consolatory gifts (mut’ah). This inconsistency suggests that legal protection for women remains a potential "geographic lottery," heavily dependent on the judicial paradigm within each jurisdiction. Furthermore, this study finds that the success of mediation in divorce cases cannot be measured solely through quantitative metrics, as women often hold weak economic bargaining power during family negotiations. The issuance of Supreme Court Circular (SEMA) No. 1 of 2022 provides a legal basis for judges to exercise ex officio authority in determining maintenance, even in the husband's absence (in absentia). This study concludes that the transformation of gender-responsive Islamic family law requires standardised application of norms and enhanced judicial sensitivity to ensure that the economic rights of women in mafqud cases are protected consistently and equitably across all Religious Courts in Indonesia.